2020
DOI: 10.1051/e3sconf/202021018023
|View full text |Cite
|
Sign up to set email alerts
|

The educational potential of technical university educational space: system-activity aspect

Abstract: Purposes of the work: 1) to reveal the educational potential of technical university educational space; 2) to consider the transfer mechanisms of cultural and historical experience from the point of view of the system-activity approach. Methodology. The educational potential of a technical university is revealed with the help of the methodological tools of social and psycho-pedagogical disciplines. Results. The article substantiates the need to present new requirements for the formation of an upbringing educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Solzhenitsyn». The presented graffiti have a dialogical character and, expressing the concept of connection between generations of different eras, acquire not only intimate and personal, but also agitational and invocative communicative intentions: the direct duty of modern society is to preserve immutable spiritual and moral guidelines and moral and ethical and values [7].…”
Section: Resultsmentioning
confidence: 99%
“…Solzhenitsyn». The presented graffiti have a dialogical character and, expressing the concept of connection between generations of different eras, acquire not only intimate and personal, but also agitational and invocative communicative intentions: the direct duty of modern society is to preserve immutable spiritual and moral guidelines and moral and ethical and values [7].…”
Section: Resultsmentioning
confidence: 99%
“…The methodology of the presented scientific research is based on research on changes in the media sphere (convergent journalism), updates of information presentation formats, transformation of genre and style [7][8][9][10]; on the principles of popularization of science at the present stage [11]; on the principles of epistemic modality, evidentiality [12] and author's responsibility, in particular, of the addressee-scientist/ addressee-researcher, scientist [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive data has shown that even the differentiation of vowel sounds pronounced by native speakers has a great impact on the vocabulary of a child or future social communicator [6]. Therefore, communicative efficiency is reduced when communicating with people who have various phonetic features or accents that are typical for speakers of different nationalities.…”
Section: Improving Communication Skills On Variousmentioning
confidence: 99%
“…The symbolic or coded format of communication has long attracted researchers dealing with the intergenerational transmission of knowledge [3][4][5]. However, it was the identification of the possibility of superimposition of new concepts on concepts already known to man that became the starting point for understanding the process of intercultural communication [6]. On the basis of existing patterns of human behavior in the communicative process, we highlight the emerging new behavioral patterns in which man is becoming less and less involved, leaving a constantly increasing range of actions for machines: robots, computers, various mechanisms.…”
Section: Introductionmentioning
confidence: 99%